High Density Planting in Mango cv. Alphonso - Dalvi, N V; Salvi, B R; Chavan, S A; Kandalkar, M P (Journal of Horticultural Sciences, 2010)
A trial was conducted to optimize spacing for high density planting in mango cv. Alphonso to obtain higher yield/ unit area at the Agriculture Research Station, Mulde, during 2006-07 to 2008-09 with four close spacings and one normal spacing as control. Highest yield (6.4 MT/ha) was recorded with a spacing of 5 m x 5 m without reduction in fruit size in 10 year old plants compared to the mean yield of 1.12 MT/ha in 10m x 10m normal spacing. High density plantation helped to get significantly higher yield per unit area compared to the normal spacing, without affecting size and quality of mango fruits. The highest cost:benefit ratio (2.33) was recorded in high density plantation of 5m x 5m, with maximum net returns of Rs.1,12,000/- per hectare. The present findings show promise for more yield and returns per unit area during the initial years of mango plantation by adopting 5m x 5m high density planting.
Keywords: Mango; Alphonso; Spacing; High Density Planting